2016
DOI: 10.1101/gad.270009.115
|View full text |Cite|
|
Sign up to set email alerts
|

The evolutionary turnover of recombination hot spots contributes to speciation in mice

Abstract: Meiotic recombination is required for the segregation of homologous chromosomes and is essential for fertility. In most mammals, the DNA double-strand breaks (DSBs) that initiate meiotic recombination are directed to a subset of genomic loci (hot spots) by sequence-specific binding of the PRDM9 protein. Rapid evolution of the DNA-binding specificity of PRDM9 and gradual erosion of PRDM9-binding sites by gene conversion will alter the recombination landscape over time. To better understand the evolutionary turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
281
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(316 citation statements)
references
References 65 publications
23
281
0
2
Order By: Relevance
“…One of the current explanations is that Prdm9 is under positive selection, associated with the rapid evolution of its binding sites [Coop and Myers, 2007;Oliver et al, 2009;Thomas et al, 2009;Myers et al, 2010]. In fact, both SNPs and short indels can induce the appearance of novel hotspots, at an estimated rate of 0.7-1.4 DSBs every 1,000 generations, as recent studies have shown in mice [Smagulova et al, 2016]. However, and despite the importance of the Prdm9 gene in modulating recombination, the existence of species such as dogs and finches [Axelsson et al, 2012;Muñoz-Fuentes et al, 2015;Singhal et al, 2015] lacking either the gene or a functional PRDM9 protein suggests the exis-Since meiotic recombination strongly influences genome evolution, mammalian recombination landscapes can be considered as a reflection of the selective forces that affect the DNA sequence itself (determined by population genetics and the evolutionary history of each taxon), the chromosomal/genome distribution of COs, and how the DNA is packaged into chromosomes during meiosis.…”
Section: Genetic and Epigenetic Marks Of Dsbs And Recombination Hotspotsmentioning
confidence: 95%
See 3 more Smart Citations
“…One of the current explanations is that Prdm9 is under positive selection, associated with the rapid evolution of its binding sites [Coop and Myers, 2007;Oliver et al, 2009;Thomas et al, 2009;Myers et al, 2010]. In fact, both SNPs and short indels can induce the appearance of novel hotspots, at an estimated rate of 0.7-1.4 DSBs every 1,000 generations, as recent studies have shown in mice [Smagulova et al, 2016]. However, and despite the importance of the Prdm9 gene in modulating recombination, the existence of species such as dogs and finches [Axelsson et al, 2012;Muñoz-Fuentes et al, 2015;Singhal et al, 2015] lacking either the gene or a functional PRDM9 protein suggests the exis-Since meiotic recombination strongly influences genome evolution, mammalian recombination landscapes can be considered as a reflection of the selective forces that affect the DNA sequence itself (determined by population genetics and the evolutionary history of each taxon), the chromosomal/genome distribution of COs, and how the DNA is packaged into chromosomes during meiosis.…”
Section: Genetic and Epigenetic Marks Of Dsbs And Recombination Hotspotsmentioning
confidence: 95%
“…First, the overlap between DSB initiation sites in the 6 different mice strains ranged from 1.1 to 34%, based on ZnF domain sequence similarity [Smagulova et al, 2016]. More importantly, novel DSB initiation sites are generated in hybrids which are heterozygous for different Prdm9 alleles in a frequency that ranges from 2 to 35%, most probably attributed to the appearance of novel polymorphisms in the parental genomes.…”
Section: Genetic and Epigenetic Marks Of Dsbs And Recombination Hotspotsmentioning
confidence: 99%
See 2 more Smart Citations
“…DMC1 binds to single-strand DNA generated by DSB end processing (Smagulova et al 2011). By use of this approach, it was shown, in mice and humans, that PRDM9 variants with different zinc finger arrays specify distinct, essentially not overlapping, sets of meiotic DSB sites throughout the genome Pratto et al 2014;Smagulova et al 2016). PRDM9, which belongs to the PRDM family of transcription regulators (Fog et al 2012), has homologs in most mammals with the exception of Canidae.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%